Representation of solutions of nonhomogeneous conformable fractional delay differential equations - Mahmudov, Nazim, I; Aydin, Mustafa (Pergamon-Elsevier Science Ltd, 2021)
A B S T R A C T This paper is about the conformable fractional delay equations. We offer a conformable delay perturbation of matrix exponential function to give the representation of solutions for linear nonhomogeneous conformable fractional delay differential equations. Lastly, the existence and uniqueness of solutions and Ulam-Hyers stability of the equations are proved. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Conformable derivative; Conformable delay perturbation; Representation of solutions; Existence; Ulam-Hypers stability